Determinants of stock returns in the property and real estate sector on the IDX in 2018-2023 - Nurul Habibah; Arista Natia Afriany; Ahsan Sumantika (Proceeding International Conference on Accounting and Finance, 2025)
This research aims to examine the influence of earnings per share, current ratio, debt to asset ratio, and return on assets on stock returns of property and real estate companies listed on the IDX in 2018-2023. The population in this research is property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2023 period. Using the purposive sampling technique in sampling, 27 companies were obtained as research samples, resulting in 162 data. This research is quantitative research with secondary data. Data collection was carried out using the documentation method and data analysis was carried out using multiple linear regression analysis. The results of this research show that earnings per share and return on assets have a negative and insignificant effect on stock returns, the current ratio has a positive and insignificant effect on stock returns, and the debt to asset ratio has a significant negative effect on stock returns.